Briquetting characteristics of bean straw-maize cob blend. (July 2019) - Okot, David K.; Bilsborrow, Paul E.; Phan, Anh N.
Abstract: Bean straw briquettes exhibited high quality in terms of density, impact resistance and compressive strength. The impact resistance was above 96% for a particle size up to 4 mm and pressures as low as 100  MPa at a compacting temperature of 80 °C. Reducing the compacting temperature required higher pressure and smaller particles to obtain similar quality briquettes. There were strong interactions between briquetting parameters with the pressure × temperature interaction significantly affecting both density, impact resistance and compressive strength. Adding bean straw significantly improved the mechanical properties of maize cob briquettes produced at low pressure and from larger particle size. From a practical and energy point of view, a temperature of 80 °C should be used for briquetting to reduce energy inputs (pressure and grinding) as this low temperature could be obtained directly from industrial waste heat. Highlights: The interaction between temperature and pressure strongly influenced properties of briquettes of bean straw and blends of bean straw/maize cob. High quality of bean straw briquettes could be achieved at low pressures and large particle sizes. Adding bean straw enhanced significantly mechanical properties of blends of maize cob and bean straw due to mechanical interlocking bonding.